Gender and age specifics of clinical status, structure-functional parameters of the heart, and their relationship with psychoemotional state of patients with chronic heart failure after myocardial infarction - G. M. Dadashova (Кардиоваскулярная терапия и профилактика)
Aim. To assess gender and age specifics of clinical status, its relationship with psychoemotional state, assessment of structure-functional parameters of the heart in patients with chronic heart failure (CHF) after myocardial infarction (MI).Material and methods. Totally, 310 patients (160 men, 150 women) studied, at the age 45-75 y.o., with CHF of II-III functional classes (FC) and postinfarction cardiosclerosis, hospitalized to SRI of Cardiology of Azerbaijan in the year 2013. All patients were selected to 4 groups according to gender and age: 1 group (n=70) males with mean age 54,8±0,6 y.; 2nd group (n=80) women, mean age 58,0±0,3 y.; 3rd group (n=90) males, mean age 63,6±0,4 y.o., 4th group (n=80) women, man age 68,4±0,3 y.o. All patients underwent basic clinical assessment, life quality by Minnessota score, brain natriuretic peptide, depression level via Hamilton score, and echocardiography (EchoCG).Results. By the results, there were some differences between males and females with CHF. Males showed more frequently Q-MI. Females had more prevalent arterial hypertension (AH) comparing to males, 93,3% vs 68,1%, respectively (p<0,001). Women with CHF, after MI, had more prominent sympthoms of heart failure, and probably related to this, more significant restriction of exercise tolerance. Life quality by Minnesota score and Hamilton depression levels were significantly worse in women than in men (p<0,001). Among women obesity was significantly more prominent (p<0,001). During morphofunctional parameters analysis of the heart by EchoCG data, linear and volumetric parameters were significantly higher in men. Ejection fraction of the left ventricle in women was significantly higher. Women significantly more commonly had concentric hypertrophy of the left ventricle comparing to other types of heart remodeling.Conclusion. Severity of CHF in men was mostly determined by functional-morphologic characteristics of myocardium, in contrast to women, who have also significant patterns of anxiety and depression. By the data from EchoCG it is found, that linear and volumetric parameters are significantly higher in men, and left ventricle ejection fraction is significantly lower than in women. Women with CHF significantly more common concentric type of hypertrophy of the left ventricle comparing to other types of the heart remodeling.